Experiências de um estágio profissional: O percurso formativo de um futuro Professor de Educação Física - Rui Miguel Ferreira Oliveira (2022)
The school placement is part of the study plan of the 2nd year of the Master's Degree in Teaching Physical Education in Primary and Secondary Schools, Faculty of Sports, University of Porto. This school placement allows the student trainee to have an experience of what is the teaching of Physical Education in schools accompanied by experienced professionals, a cooperator at the school and a faculty supervisor. This document is called school placement and it describes the whole process, all the experiences lived and all the knowledge acquired during the school year. A year full of learning, enriching experiences and problem solving. In this report I present all the strategies used, all the planning and the students' accountability in the learning process. After complicated years, where there were several lockdowns, this year was a year where that did not happen and as such all classes were face-to-face. A great importance was given to contacting my students with as many sports as possible. In the 1st term the main focus was to identify the problems of my performance as a teacher. In the 2nd term I managed to solve all the problems through all the strategies used. The 3rd term was a time to enjoy my classes. In the study I could understand the biggest gaps in my class in a specific modality and I could identify problems in my teaching. I end with a reflection of this very enriching experience